Pesan Dakwah dalam Novel "99 Cahaya di Langit Eropa" - Moh. Slamet; Ovanda Ayu Kristiyanti (Menara Tebuireng, 2018)
The problem examined in this research is the preaching message in the novel â€œ99 Cahaya di Langit Eropaâ€. To answer the problem, the researcher used qualitative research methods with descriptive approach. The data is analyzed by using the Roland Barthes semiotic analysis, this method is one of the media text analysis methods. From the research result, it can be concluded that the preaching message in this novel focuses on the moral message shown by being a good Muslim agent who fosters peace honestly, friendly, generous, and good behavior. In addition, social messages are also implied by being tolerant to people who have different beliefs, races, ethnicities, and cultures. Understanding each other's differences and looking for something that can unite differences will make life more beautiful and harmonious